Effect of moderate heat stress on tuberization of potato genotypes: Morphological and physiological changes using in vitro and ex vitro propagation - Delgado-Paredes, Guillermo E. (2024)
Potato plants are often subjected to heat stress during growth and development, resulting in loss of yield and quality. However, the possibility exists that commercially important genotypes show tolerance to heat stress. In this study, we aim to investigate the morphological and physiological effects of moderate conditions of heat stress on tuberization in nine potato genotypes, and how it affects propagation using an ex vitro and in vitro system. The plant material came from the In Vitro Germplasm Bank of the International Potato Center (CIP). The incubation temperatures of the cultures in in vitro and ex vitro conditions were the ambient in the laboratory and greenhouse, respectively. In in vitro system a randomized complete block design was employed in nine genotypes, two treatments: multiplication culture medium and the same culture medium supplemented with 8.0% sucrose and 500 mg/L-1 CCC, six flasks and five explants per experimental unit. Among all genotypes evaluated, Leona and Liberteña did not form tubers under ex vitro treatment conditions. Under in vitro conditions, Amarilis, Capiro, Perricholi and Tacna showed no evidence of tuberization, and Canchán was the only genotype where 100% formation of tuberous structures were produced in all evaluations. The findings concluded in this study showed that of all the potatoes evaluated, Canchán best responded to the evaluations under both in ex vitro and in vitro conditions, at maximum temperatures between 22.4 to 26.9 and 27.0 to 28.2 oC, respectively. Therefore, it is vitally important to consider its development potential in different producing locations around the world, which are directly and indirectly affected by climate change.